1999
DOI: 10.1038/sj.bjc.6690497
|View full text |Cite
|
Sign up to set email alerts
|

Expression of oestrogen and progesterone receptors in gastric cancer: a flow cytometric study

Abstract: Summary Increased expression of oestrogen (ER) and progesterone (PR) receptors have been reported in gastric adenocarcinoma, although results have been variable. Immunohistochemical staining methodologies, in particular in the detection of ER, have been inconsistent with many tumours being classified ER-negative. In this study we have used flow cytometry to quantify expression of ER and PR in gastric adenocarcinoma and examine their relationships with established prognostic indicators. Cytokeratin-positive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
8
0
3
Order By: Relevance
“…Estrogens regulate numerous physiological processes primarily by binding to estrogen receptors, which are potent transcriptional regulators 35. As estrogen receptors are present in gastric epithelial tissue11 13 and have been shown to inhibit inflammation,3638 it is biologically plausible that estrogens could protect against gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogens regulate numerous physiological processes primarily by binding to estrogen receptors, which are potent transcriptional regulators 35. As estrogen receptors are present in gastric epithelial tissue11 13 and have been shown to inhibit inflammation,3638 it is biologically plausible that estrogens could protect against gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…First, the estrogen receptor, progesterone receptor, and androgen receptor, transcriptional regulators that bind to steroid hormones and exert their actions, are expressed in normal and cancerous gastric tissue 1113. Second, male rats are more likely to develop gastric cancer after carcinogen exposure than are female rats 14 15.…”
mentioning
confidence: 99%
“…Previous studies have suggested that the steroid hormone-mediated signaling pathway has an important role in the progression of gastric cancer [20][22]. Of the hormones implicated in relating to gastric cancer, estrogen was reported to be closely involved in gastric cancer carcinogenesis and development.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of E2 and P4 have been evaluated on several different tissues and cell types. Although information about E2 and P4 effects on gastric tissue is scarce, E2 and P4 receptors have been found in the normal human stomach, gastric cancer tissues, and cell lines [35–37]. In the intact rat stomach, differential expression of E2 receptor isoforms α and β in gastric antrum and fundus has been observed.…”
Section: Discussionmentioning
confidence: 99%